2004
DOI: 10.1016/j.jacc.2003.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome (up to 15 years) of balloon angioplasty of discrete native coarctation of the aorta in adolescents and adults

Abstract: Long-term results of BA for discrete AC are excellent and should be considered as first option for treatment of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(38 citation statements)
references
References 35 publications
1
34
0
3
Order By: Relevance
“…They concluded that results in young adults are similar to those observed in children; balloon angioplasty should be considered as an option to surgical intervention; and follow-up studies (longer than 1 year) are required. Other reports followed [22][23][24][25][26][27][28][29][30][31][32][33], which are tabulated in Table 1. Based on the review of these publications, the conclusion drawn by Attia and Lababidi [21] are appropriate but, aortic perforation and dissection during the procedure and aneurismal formation at follow-up are also seen in adults.…”
Section: Results In Adult Patientsmentioning
confidence: 99%
“…They concluded that results in young adults are similar to those observed in children; balloon angioplasty should be considered as an option to surgical intervention; and follow-up studies (longer than 1 year) are required. Other reports followed [22][23][24][25][26][27][28][29][30][31][32][33], which are tabulated in Table 1. Based on the review of these publications, the conclusion drawn by Attia and Lababidi [21] are appropriate but, aortic perforation and dissection during the procedure and aneurismal formation at follow-up are also seen in adults.…”
Section: Results In Adult Patientsmentioning
confidence: 99%
“…In the last 10 years, there has been an explosion of reports of endovascular stenting and/or angioplasty of native coarctation in the adult (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Most of these reports cite good angiographic results and a decrease in the transcoarctation pressure gradient but have very short follow-up and do not discuss the most clinically relevant factor: cure of hypertension.…”
mentioning
confidence: 99%
“…Another study which done in Riyadh Saudi Arabia, concluded that the doppler COA gradient across the COA site decreased from 57.6 ± 17.7 mmHg to 16.6 ± 8.4 mmHg one year after angioplasty [34].…”
Section: Discussionmentioning
confidence: 98%